Effectiveness of Murattal Therapy in Reducing Anxiety in Diabetics - Siti Nur Asiyah; Imamah Istikhomah (AIUA Journal of Islamic Education, 2019)
The purpose of this study was to determine the effectiveness of murattal al- qur’an therapy in reducing anxietyin people with diabetes mellitus. This research is quantitative research wiht exprerimental methods that use data collection techniques in the form of anxiety scale. Subjects in this study amounted to 15 people who underwent in patient at RSUD dr. H. Slamet Martodirdjo Pamekasan with criteria of people wiht diabetes mellitus who have high anxiety. Selection of subject by giving an anxiety scale to everyone with diabetes mellitus who is undergoing hospitalization in hospitals in October. The results of the scale calculation and then made the norm with theformula interval to categorize the anxiety of high and low. Of the 15 people who were selected to be the subjects of the past research will undertake the murattal al-qur’an treatment. The result is effective in reducing anxiety inpeople with diabetes mellitus.